Dwi Fungsi Media Massa - Habibie, Dedi Kusuma (Interaksi: Jurnal Ilmu Komunikasi, 2018)
Mass media should provide constructive information in order to full fill its function as a tool for developing nations. However, mass media usually face a conflict of interest in doing the role, for example in the Indonesian case there is a strong political economy interest of media owner that limiting media’s role as political control. This study sees those is a crucial problem of Indonesian media as it will decrease the quality of Indonesian media and as the consequences, it will lose public trust. By using descriptive qualitative method this article doing a theoretical review to explain the role of Indonesian media in the political communication and how the media doing their role as information and political channel in the political communication process. This study suggests the media do a role called ‘dwifungsi media’ that suggest media to do its function comprehensively.